Peningkatan Kapasitas Masyarakat Desa Gema Dalam Pengawasan Mutu Infrastruktur Melalui Bimbingan Teknis Berbasis Partisipatif - Alan Putranto; Suratmin Suratmin; Julyan Purnomo; Muhammad Hanif Faisal; Nely Kurnila; Firmanilah Kamil; Ahmad Ravi; Nur Aida; Saima Putrini R. Harahap; Khairul Muttaqin; Rabiya Rabiya; Syf. Umi Kalsum; Hurul ‘Ain; Syf. Mastura (Pengelola Jurnal Politeknik Negeri Ketapang Jl. Rangga Sentap, Dalong Sukaharja, Ketapang 78813. Telp. (0534) 3030686 Kalimantan Barat, 2026)
Gema Village, located in Simpang Dua District, Ketapang Regency, has significant potential in agriculture and plantation sectors but faces challenges in infrastructure quality control. This Community Service Program (PKM) aims to strengthen the technical capacity of village officials and the community in conducting effective, transparent, and sustainable construction quality supervision. The implementation methods include quality policy socialization, case-based technical training, application of on-site quality checklist systems, direct mentoring during construction activities, and performance-based evaluation. The results indicate a notable improvement in technical knowledge (from 54.3% to 79.4%), ability to create quality checklists (from 35% to 85%), and participant satisfaction (92%). The Village Empowerment Institution (LPM) is now capable of performing independent and documented quality control. The study concludes that nonformal education-based approaches significantly enhance technical literacy and infrastructure governance in rural areas. It is recommended that similar programs be conducted periodically with cross-institutional collaboration to ensure sustainability and replication of the PKM model in other villages.